Salvia miltiorrhiza in Breast Cancer Treatment: A Review of Its Phytochemistry, Derivatives, Nanoparticles, and Potential Mechanisms - Zhao, Huan; Han, Bing; Li, Xuan; Sun, Chengtao; Zhai, Yufei; Li, Man; Jiang, Mi; Zhang, Weiping; Liang, Yi; Kai, Guoyin (Frontiers in Pharmacology, 2022)
Breast cancer is one of the most-deadly malignancies in women worldwide. Salvia miltiorrhiza, a perennial plant that belongs to the genus Salvia, has long been used in the management of cardiovascular and cerebrovascular diseases. The main anti-breast cancer constituents in S. miltiorrhiza are liposoluble tanshinones including dihydrotanshinone I, tanshinone I, tanshinone IIA and cryptotanshinone, and water-soluble phenolic acids represented by salvianolic acid A, salvianolic acid B, salvianolic acid C and rosmarinic acid. These active components have potent efficacy on breast cancer in vitro and in vivo. The mechanisms mainly include induction of apoptosis, autophagy and cell cycle arrest, anti-metastasis, and formation of cancer stem cells, and potentiation of antitumor immunity. This review summarized the main bioactive constituents of S. miltiorrhiza and their derivatives or nanoparticles that possess anti-breast cancer activity. Besides, the synergistic combination with other drugs and the underlying molecular mechanisms were also summarized to provide a reference for the future research of S. miltiorrhiza for breast cancer treatment.